Phylogenetic History of Kara Kum Desert Focus - G. A. Eroshenko; L. M. Kukleva; Zh. V. Al’khova; A. N. Balykova; N. V. Popov; Ya. M. Krasnov; N. S. Chervyakova; V. V. Kutyrev (Проблемы особо опасных инфекций, 2020)
Objective of the study was to analyze phylogenetic relation of the strains and dissemination routes of Yersinia pestis in Kara Kum desert focus in XX century.Materials and methods. We have carried out whole genome sequencing of 8 Yersinia pestis strains isolated in Kara Kum desert focus between 1949 and 1985. We also used nucleotide sequences of 16 Y. pestis strains from neighboring foci of East and North Caspian Sea region dated 1917–2002, sequenced at the premises of RusRAPI “Microbe” on Genestudio Ion S5XL platform (Thermo Fischer Scientific). Phylogenetic analysis was performed based on 1720 identified core SNPs. Phylogenetic dendrogram was constructed using Maximum Likelihood algorithm, PhyML v. 3.1 software package, and nucleotide substitution model GTR.Results and discussion. On the basis of whole-genome SNP analysis of Y. pestis strains from Kara Kum desert focus, West and North Caspian Sea region foci analysis of plague agent populations circulating in Turkmenistan in XX century was conducted. It has been demonstrated that three separate waves of Y. pestis dissemination swept the territory of Kara Kum desert focus. The origin of the first one, registered in 1912, plague outbreak in south-eastern part of the focus and its etiological agent remain unspecified so far. The second wave is associated with distribution of North-Aral 2.MED1 population of medieval biovar in 1949–1970, which led to the emergence of epizootic activity in 1949, as well as subsequent cases and outbreaks of plague in this territory in the middle of the XX century. In the mid-second half of the past century, one more 2. MED1 dissemination wave from the North Balkhash region hit the Kara Kum desert focus. This central-asian  population has also taken root in the natural biocoenosis of the Kara Kum focus. The data obtained testify to active processes of distribution of Y. pestis of medieval biovar in East Caspian Sea region in southern sub-zone of Eurasian deserts in XX century.